How existing things are invariably present as sense? - Listik, Yonathan (Intuitio, 2019)
This article aims to explore Jean-Luc Nancy’s notion of sense as a key ontological concept. This concept, as it appears mainly in his Sense of the World (1997b), opens the possibility of a more profound understanding of his thesis. The effort in this article will not be an attempt to draw a map or a line in Nancy’s theory placing sense either as the starting point or as his central concept. Instead, it is an attempt to show that sense plays a significant role in Nancy’s understanding of world and finitude, as it becomes evident is his recurrent concern with Wittgenstein’s (1994) aphorism 6.41: that the sense of the world must stand outside the world. Nancy defines the world as a rapport of entities or existents to each other. So, the argument advanced here analyzes sense’s centrality to Nancy´s discussion on touch and the vital role touch has in the articulation between his comprehension of mitsein/être-avec and his elaboration of being as singular plural, in order to show that a focus on sense could bring forwards a relevant elucidation of Nancy’s ontological argument and its implications. *** Como as coisas existem como sentido *** Esse artigo tem como objetivo explorar de que maneira a noção de sentido é um conceito ontológico central na filosofia de Jean-Luc Nancy. Esse conceito, como ele aparece em Sense of the World (1997b), abre a possibilidade para um entendimento mais profundo de sua tese. Esse artigo não busca percorrer ou desenhar um mapa, ou ainda, uma linha, através da filosofia de Nancy, cujo o sentido se colocaria como ponto de partida ou como conceito central.O artigo mostra que sentido tem um papel fundamental na compreensão de Nancy sobre os conceitos de mundo e finitude, como é exemplificado, pelo autor, em sua análise do aforismo 6.41 de Wittgenstein (1994): o sentido do mundo deve estar fora do mundo. Nancy define mundo como relação entre entidades ou existências entre si. O ponto defendido aqui é que a centralidade do sentido para Nancy se apoia em sua discussão acerca do toque e em seu papel central na articulação entre mitsein/etre-avec. Tais conceitos, se considerados em paralelo a noção de ser singular-plural, podem iluminar a ontologia defendida por Nancy. Palavras-chave: Sentido. Ontologia. Desconstrução. Tocar. Estar com